Ten promising pathways to GHG emission reduction in the global food system - Pingault, N.; Martius, C. (CIFOR-ICRAF, 2023)
Global average surface temperatures are now 1.09°C higher than in pre-industrial era, with greenhouse gas emissions (GHGE) from human activities unequivocally identified as the main driver behind this global warming. In 2018, the global food system emitted 13-23 GtCO2eq per year, or 23-42% of total net anthropogenic emissions. Without a radical transformation of the food system, it may be impossible to reach the Paris Agreement goal of limiting global warming to 1.5/2.0°C. Following the IPCC guidelines, data on GHG emissions are generally collected and analyzed by economic sectors (Energy, Industry, AFOLU, Waste). Moving away from this sectoral perspective, this paper suggest to adopt a holistic view covering the whole food supply chain from farm to fork. This paper reviews ten promising pathways to GHG emission reduction in food systems: shifting diets; improving waste management, energy use in value chains, cold-chain efficiency; reducing enteric fermentation; improving manure management, fertilizer manufacturing emissions, rice cultivation, soil organic carbon; and encouraging agroforestry. It assesses their technical and economic mitigation potentials, the synergies and trade-offs across mitigation options and development goals, as well as the stumbling blocks for implementation, and suggests ways forward. These suggested pathways are intended to trigger a debate and open up avenues to a rapid drawdown of GHG emissions, by taking a holistic view to the global food system, one of the largest GHG-emitting sectors in the planet. This paper shows the very important mitigation potentials of demand-side options like changes in diets and reduction of food losses and waste. This highlights our individual and collective power as citizens and consumers to re-orient our food systems by changing our consumption habits and behaviors. It is not too late.